185k views
1 vote
F(x) = 3x + 10
g(x) = x - 2
Find f(g(5))

1 Answer

4 votes

There are a couple ways we can solve this:

1. We can plug in g into f and then make x = 5


3x+10\\3(x-2)+10\\3x-6+10\\3x+4\\plug.in.5\\3(5)+4\\15+4\\19

So f(g(5)) = 19

2. We can plug in g pre-solved with x = 5 into f


x-2\\5-2\\3\\plug.in.3.into.f\\3x+10\\3(3)+10\\9+10\\19

So again, f(g(5)) = 19

As you can see, either way works fine. it just depends on what makes more sense to you personally.

User Thispatchofsky
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.